Role of financial architectonic in support of development of economic systems - Kotkalova-Lytvyn, Inna (Skhid, 2016)
Article studies level of influence of financial architectonic to the economic systems development. The essence of economic category "financial architectonic" is revealed, its characteristics are determined, namely: represents set of elements of financial system; is an integral system of the financial space; distribution and redistribution of financial resources and capital; has ability of renovation and qualitative changes according to challenges of globalization processes. Scientific heritage of such scholars as T. Beck, M. Miller, R. Levin, R. Lucas, J. Robinson, J. Schumpeter, were considered for determination of influence degree of financial mechanisms to economic growth. Conducted research allowed to obtain following results: banks, non-banking financial institutions and equity markets are more developed in rich countries with strong economies; effectiveness and depth of the national financial architectonic directly affects labor productivity and national wealth accumulation, representing key factor in the development of economic systems.